Analisis Dismilaritas Kinerja Keuangan Perbankan Konvensional dan Perbankan Syariah di Indonesia - Hutajulu, Rina Noni (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This research goals to analyze whether there are dissimilarity in financial performance between the two types of banking in Indonesia. The research method used in this research is descriptive qualitative with a quantitative approach, where the population in this research is conventional banking and sharia banking listed on the Indonesia Stock Exchange, while the samples in this research are the four largest conventional banks and the four largest sharia banks in Indonesia. In carrying out hypothesis testing, this research used descriptive statistical analysis and the T-test and Wilcoxon test. In this research, the results showed that there was no significant dissimilarity in the financial performance of the two banks for each financial ratio used.